Investigating platelet-activating factor as a potent proinflammatory mediator in coronary atherosclerotic patients - Raheem, Shler Ghafour (Cellular and Molecular Biology, 2021)
The inflammatory reaction is one of the complications in patients with coronary atherosclerosis. This study aimed to determine the diagnostic value of platelet-activating factor (PAF) compared with high sensitivity C reactive protein (hs-CRP) in coronary atherosclerotic patients. Fifty patients with coronary atherosclerosis and 30 subjects with normal angiography were considered as the control group attending Cardiac Center-Surgical Specialty Hospital - in Erbil city / Iraq. The levels of PAF and hs-CRP were estimated quantitatively using a sandwich enzyme-linked immunosorbent assay and a particle-enhanced immune turbid metric assay, respectively. Lipid profiles and some hematological indexes were also used in this study. The levels of the inflammatory biomarkers of PAF and hs-CRP increased significantly in the patients group compared with controls (p<0.05). Although the patients group showed the highest level of low-density lipoprotein (LDL), the difference was not significant (p>0.05) compared with the healthy control. However, the incidence of risk factors such as smoking and obesity showed a significant difference (p<0.05) in the patients group. Additionally, the PAF level correlated positively and significantly with hs-CRP (p<0.05), and negatively with high-density lipoprotein (HDL) (p>0.05). Although hs-CRP was a valuable diagnostic marker for coronary atherosclerosis, the PAF level showed to be a better prognostic indicator than hs-CRP in coronary atherosclerosis patients.